Beneficial effect of the leaves of Murraya koenigii (Linn.) Spreng (Rutaceae) on diabetes-induced renal damage in vivo - Yankuzo, Hassan; Ahmed, Qamar Uddin; Imam Santosa , Rahajoe; Akter, Seikh Farid Uddin; A.Talib, Norlelawati (Elsevier Ireland Ltd, 2011)
Ethnopharmacological relevance: Murraya koenigii (Linn.) Spreng (curry leaf) is widely used as a nephroprotective agent in kidney’s infirmities among diabetics by the traditional practitioners in Malaysia. However, the latter role of curry leaf has been grossly under reported and is yet to receive proper scientific evaluation. Aim of the study: The present study was designed to investigate the beneficial effect of the leaves of Murraya koenigii (Linn.) on diabetes-induced renal damage in vivo with regard to prove its efficacy by local traditional practitioners in the treatment of kidney frailties in diabetics. Materials and methods: Aqueous (AQ) extract of the leaves of Murraya koenigii (Linn.) was administered to both normal and streptozotocin (STZ) induced diabetic male rats (Sprague–Dawley strain). Animals were divided into six groups (n = 6) and treated with variable dose levels ofAQextract (200 and 400 mg/kg body weight/day) for 30 days. At the end of 30 days, animals were sacrificed, blood was collected, processed and stored at −70 ◦C for the zestimation of serum urea and creatinine, changes in plasma antioxidant capacity by FRAP assay, and glutathione peroxidase levels, in the normal and STZ-induced diabetic rats. Histological changes of the kidneys of these animals were also evaluated by light microscopy to determine the beneficial effect of the leaves. Results: Daily oral administration of variable dose levels of theAQextract for 30 days, produced significant dose dependant decrease in serum urea and creatinine levels (p < 0.001), and marked increase in the levels of plasma antioxidant capacity (p < 0.01) in diabetic treated rats, compared to the control (nondiabetic) subjects. However, the normal treated rats showed minimal variation in these parameters in comparison to normal controls. Histological studies of the kidneys of these animals showed comparable tissue regeneration by the AQ extract. Conclusion: The results of our study scientifically support the traditional belief for using the leaves of Murraya koenigii (Linn.) as adjuvant, in the treatment of pain disorders related to renal impairments among diabetics.